A New Traceless Technique for Cosmetic Closure of Minimally Invasive Incision and Chest Tube Fixation After Uniportal Video-Assisted Thoracoscopic Surgery - Chen, Zihao; Xin, Ning; Huang, Kenan; Wei, Rongqiang; Liu, Chengdong; Niu, Shiwen; Xu, Zhifei; Ding, Xinyu; Tang, Hua (Frontiers in Surgery, 2022)
Background As uniportal VATS becoming mainstream, how to make the incision cosmetic has attracted much attention. This study aimed to introduce a new traceless method for cosmetic closure of the incision and a special procedure for chest tube fixation after uniportal VATS and to evaluate the feasibility, effectiveness, and safety of this new technique. Methods In this retrospective study, a total of 258 consecutive patients who underwent uniportal VATS were included. Among them, 127 patients were treated with a conventional method, and 131 patients were performed with a new method. Results Patients in the new method group had a significantly less incidence of subcutaneous emphysema after the chest tube was removed. The incidence of pneumothorax after the chest tube was removed and fat liquefaction of chest incision was not significantly different between the two groups. No differences in the incidence of pneumothorax after chest tube removal and fat liquefaction of post-surgical incision were found between the two groups. Additionally, there was also no significant difference in follow-up items. Conclusions Taken together, our results showed that this new method for minimally invasive incision closure and chest tube fixation after uniportal VATS was as feasible, effective, and safe as the conventional one but more cosmetic.